Diversity of Amylase-Producing Bacillus spp. from “Tape” (Fermented Cassava) - BARUS, TATI; KRISTANI, AMANDA; YULANDI, ADI (Bogor Agricultural University, Indonesia, 2013)
Fermented cassava or “Tape” is one of traditional Indonesian fermented food. The quality of “Tape” is determined by microorganisms involved during fermentation process. It was reported that Bacillus subtilis determined the quality of cassava “Tape”. The most common way to identify species is by using 16S rRNA gene. This gene contains conserved regions as unique sequence which is relative among species. It has been widely used as a reliable molecular marker for phylogeny identification. Therefore, the aim of this research was to study diversity of amylase-producing Bacillus spp. from “Tape” based on 16S rRNA gene sequences. Bacillus spp. were isolated from “Tape” from several area in Indonesia i.e. Jakarta, Bandung, Cianjur, Subang, Rangkas Bitung, and Kediri. Amplification of 16S rRNA gene used 63f and 1387r primers. This research showed that based on 16S rRNA gene sequences, twenty-six of amylase-producing Bacillus spp. isolates were divided into four groups. All isolates were identified as species either B. megaterium, B. subtilis, B. amyloliquefaciens, or B. thuringiensis.